2010
DOI: 10.1007/s11910-010-0170-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Status Epilepticus in Childhood

Abstract: Refractory status epilepticus (RSE) is characterized by a prolonged seizure that persists despite adequate initial management. RSE accounts for almost one quarter of all status epilepticus and carries significant risk for morbidity and mortality. Treatment varies widely between institutions regarding medication choice, dose, and monitoring. Several agents including nonanesthetic antiepileptic drugs (AEDs), anesthetic AEDs, enteral AEDs, and other therapies have been used in RSE. We review the current treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…A timely escalation of antiepileptic drugs when initial treatments fail is advocated. 9,21,39,40,87,8992 Basic research results 1416,9399 as well as clinical evidence 5,6 suggests that the longer SE persists, the more resistant it becomes to treatment. In a study of 157 children (1 month to 16 years of age) with SE, a treatment delay of more than 30 min was associated with delayed seizure control.…”
Section: Current Treatment Strategies In Pediatric Status Epilepticusmentioning
confidence: 99%
“…A timely escalation of antiepileptic drugs when initial treatments fail is advocated. 9,21,39,40,87,8992 Basic research results 1416,9399 as well as clinical evidence 5,6 suggests that the longer SE persists, the more resistant it becomes to treatment. In a study of 157 children (1 month to 16 years of age) with SE, a treatment delay of more than 30 min was associated with delayed seizure control.…”
Section: Current Treatment Strategies In Pediatric Status Epilepticusmentioning
confidence: 99%
“…There are no randomized trials for the treatment of refractory SE in children, but retrospective reviews can be found about the type of drug used (midazolam, sodium thiopental, propofol), as well as expert opinions and guidelines (Van Gestel et al., ; Morrison et al., ; Mehta et al., ; Abend & Dlugos, ; Prasad, ; Lampin et al., ; Friedman, ; Loddenkemper & Goodkin, ; Schreiber & Gaillard, ; Shearer & Riviello, ; Mastrangelo & Celato, ; Sasidaran et al., ) correct. The guidelines differ from country to country depending on the sedatives commercially available and the legislative regulations.…”
Section: Management Of Se In the Hospital Settingmentioning
confidence: 99%
“…Опубликованные режимы варьируют от 10 мк/кг/сут с последующим снижением до 1-5 мг/кг/сут на протяжении 2 дней и инициации с низких доз (1 мг/кг/сут) с последующим повышением до 6-22 мг/кг/сут в течение 3-6 дней. Первый вариант кажется авторам более предпочтительным ввиду лучшей переносимости и более быстрого развития эффекта [49,50].…”
Section: N№ 3 (97) 2018unclassified